Oil price shocks and the hedging benefit of airline investments - Jochen Güntner; Peter Öhlinger (Johannes Kepler University of Linz, Department of Economics, 2021)
In the light of finite oil reserves, Persian Gulf oil-exporting economies have recently undertaken major investments in their domestic travel and tourism industries. Building on the Bayesian SVAR model of the global oil market in Baumeister and Hamilton (2019), we investigate the conditional comovement of airline stock returns with real oil prices in response to structural oil supply and demand shocks. We find that investing in the Datastream World Airline Index offers a hedging benefit conditional on oil supply, consumption demand, and inventory demand shocks, whereas there is no evidence of systematic positive or negative comovement following shocks to world economic activity and airline stock returns.
Keywords: C32; L71; L93; Q41; 330; Airline excess returns; Bayesian SVAR model; Hedging; Oil price shocks